“Svadharma” of an Individual in the Light of Old Hindu Astronomical Thought - Monkiewicz, Marta (Vade Nobiscum, tom XXII/2021: Studia z wieków dawnych, 2021)
Vedic society of ancient India was a well-organized socio-religious structure in which each person was supposed to fulfil (mostly, or perhaps above all) religious duties, defined by person’s own social status within a particular social group, that is, to fulfil his svadharma. Dharmasūtras, texts on dharma, contain many passages specifying in detail how to perform rituals and sacrifices, and among them there are few verses which make the time of performing ritual activities dependent on observable phenomena in the sky, such as the phases of the Moon and the Sun’s daily journey through the ecliptic (ṛta). References to these insults can be found, among others in the passages on ancestral sacrifices, rituals for prosperity, and ceremonies performed while commencing and concluding Vedic studies. All describe rites performed in order to be successful in one’s own life and in the accomplishment of one’s duties, i.e. realisation of svadharma. The article gives a description of these rites, based on the original translations of chosen fragments of the source texts: Ṛgvedajyotiṣavedāṅga – the oldest Sanskrit astronomical treatise, and Dharmasūtras – codes on the law, dharma and morality.